Decay of Metastable State with Account of Agglomeration and Relaxation Processes. (5th January 2016) - Kurasov, Victor
Abstract : Theoretical description of the metastable phase decay kinetics in the presence of specific connections between the embryos of small sizes has been given. The theory of the decay kinetics in the presence of relaxation processes is constructed in analytical manner. Them -mers nucleation is investigated and the global kinetics of decay is also constructed in this case analytically.